PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN KOMPETENSI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Survei Pada Organisasi Perangkat Daerah Kabupaten Sragen) - Resti Dwi Samsiyah; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
This research accomplished to analyze the influence of goal budget clarity,accounting controls, and competence towards the performance accountability ofgovernment institution Sragen agency. The types of data collected were in form ofquantitative. The source of the data used were primary data. The technique ofdata sampling were purposive sampling. Samples were used as much 81respondents to the head of agency and the financial section. How to collect databy deploying questionnaires to the organization of the regional devices district ofSragen. Based on the test result from the research obtained in conclusion that,goal budget clarity influence has significant positive effect to performanceaccountability of government instituation, accounting control has a significantpositive effect to performance accountability of government institution,competence has a significant positive effect to performance accountability ofgovernment institution Sragen agency